2013
DOI: 10.1519/jsc.0b013e3182548af1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Indicators of Training Load in Soccer Players

Abstract: This study examined the relationship between work load indicators used to quantify full training sessions in soccer. The participants were 28 semiprofessional male soccer players age 22.9 ± 4.2 years, height 177 ± 5 cm, body mass 73.6 ± 4.4 kg. Players' physical and physiological work load was monitored over 44 training sessions using global positioning system devices (10 Hz) and heart rate, respectively. After each training session, players' training perceived-exertion (rating of perceived exertion [RPE]) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
252
10
18

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(339 citation statements)
references
References 33 publications
36
252
10
18
Order By: Relevance
“…Similar to the results of the present study, Scott et al 8 reported session RPE to be highly correlated with total distance (r = 0.80), Player load (r = 0.84), and HODO (r = 0.65) in professional soccer players. In addition, Casamichana et al 3 examined the relationship between session RPE and total distance (r = 0.76) and Player load (r = 0.74). It appears that total distance, HODO, and Player load may be viable indicators of training load in NCAA Division I soccer players.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the results of the present study, Scott et al 8 reported session RPE to be highly correlated with total distance (r = 0.80), Player load (r = 0.84), and HODO (r = 0.65) in professional soccer players. In addition, Casamichana et al 3 examined the relationship between session RPE and total distance (r = 0.76) and Player load (r = 0.74). It appears that total distance, HODO, and Player load may be viable indicators of training load in NCAA Division I soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have observed the relationship between session RPE and external loads measured using GPS technology. 3,8 These studies have reported significant correlations between session RPE and both GPS and accelerometer derived variables (r = 0.71-0.84; P < 0.01).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…11 Accordingly, the balance between training stress, competition and recovery is of significant importance so as to protect against underperformance 12 and increased injury risk 13 . Recent research in soccer and rugby has quantified aspects of weekly 14,15 , monthly 8,16,17 and seasonal 5 TL.…”
Section: Introductionmentioning
confidence: 99%
“…En esta línea, el estudio de en qué medida las tareas de entrenamiento (Casamichana et al, 2012), y de manera específica, los juegos reducidos se asemejan a la competición (Casamichana y Castellano, 2015) puede servir de gran ayuda para que los entrenadores puedan adecuar los contenidos de entrenamiento a sus propósitos. Con intención de provocar un incremento o reducción de las demandas técnicas, físicas y fisiológicas de su práctica, los entrenadores de baloncesto pueden manipular las variables de los diferentes juegos en espacios reducidos (Klusemann, Pyne, Foster, y Drinkwater, 2012).…”
Section: Introductionunclassified